Eksistensi Pertashop terhadap Kesejahteraan Masyarakat di Kecamatan Ulujami Kabupaten Pemalang - Lala Ratu Khotimah (UIN K.H. Abdurrahman Wahid Pekalongan, 2022)
Pertashop (Pertamina Shop) is a certain Pertamina sales outlet that is prepared to serve the needs of consumers of non-subsidized BBM, non-subsidized LPG and other Pertamina retail products by prioritizing their service locations in villages or cities that require Pertamina's retail product services. The presence of several Pertashop points in the district. Ulujami Kab. Pemalang has a positive impact on the welfare of the people who use fuel. The purpose of the research that the researcher will present, among others, is to determine the public interest in the presence of Pertashop, Pertashop's business opportunities, the benefits obtained by Pertashop and buyers, and the impacts obtained by the community. The benefit of this research is that the researcher hopes that this research will be information for the community and for business actors related to the common welfare. The research approach uses qualitative methods with efforts to systematically find and organize notes from observations, interviews, and others with information obtained from the community. Results and discussions include, 1) Pertashop Partnership Program from Pertamina; 2) Pertashop Business Opportunity; 3) People's buying interest; 4) Impact Occurs Due to Pertashop. The community has very high enthusiasm for the presence of Pertashop because it provides many conveniences in carrying out economic activities. The existence of Pertashop has a positive impact, among others: a) An increase in product quality is more guaranteed availability; b) The development of technology in the villages; c) Facilitate public access; d) as an additional income for the owner of Pertashop; d) Adding job vacancies in the surrounding area.